Comparison of DIC and LDV for practical vibration and modal measurements - Reu, Phillip L.; Rohe, Daniel P.; Jacobs, Laura D. (Mechanical systems and signal processing, 2017)
We compare laser Doppler vibrometry (LDV) and digital image correlation (DIC) for use in full-field vibration and modal testing. This was done using a simultaneously measured 3D displacement field on a flat 7-in. corner-supported metal plate using pseudorandom excitation via a shaker. We complete a detailed comparison between the techniques and discuss the pros and cons of each. The results show that either technique can be used for quantifying the modal information with the LDV providing better out-of-plane displacement resolution and equivalent in-plane resolution. The strain calculation is considered better in the DIC approach due to the direct tie to the surface displacements. While the LDV does not lose its place as the gold standard for modal testing, DIC has introduced a new and competitive approach that will have significant advantages in certain testing regimes.